Preparation of filter aids based on Lam Dong diatomite - Thanh Phong, Mai; Doan Minh Dang, Tran (Vietnam Journal of Science and Technology, 2017)
Diatomite from Dai Lao valley, in Lam Dong province was selected for investigation of its possible application in preparation of filter aids. For this purpose, diatomite ore was leached in acids to enrich SiO2 and reduce impurities, and then calcined at high temperatures in order to improve the material characteristics for use in filtration. The leaching was conducted in a hot 6M H2SO4 solution (90 – 95 oC) for a time period up to 36 h. To examine effects of temperature, the calcination temperature was varied in the range 900 – 1250 oC. The physical, chemical, thermal and micro–structural features of the raw and the calcined diatomite were determined to compare them with those of the commercial filter aids currently used. It is shown that the Lam Dong diatomite can successfully be used for preparation of filter aids.